Respuesta multidisciplinar de la Unión Europea ante el desafío del cambio climático - Molina Igartua, Gonzalo (Revista Española de Desarrollo y Cooperación, 2023)
The statistics relating to world primary energy consumption and emissions of Greenhouse Gases responsible for climate change are worrying, so not to implement mesures to stop global warming would caused detrimental impacts to the planet, reversible and / or irreversible, not all of equal gravity, but with a negative impact on the global economy and, ultimately, on humanity. Starting from this context, the article analyzes the European Union’s position on climate change.